2011
DOI: 10.1007/s00710-011-0173-7
|View full text |Cite
|
Sign up to set email alerts
|

Native osmium from the Guli Massif, Northern Siberia, Russia

Abstract: SummaryNative osmium from two different placer occurrences (i.e., Ingaringda and Burlakovsky) within the Guli Massif, Maimecha-Kotui Province, was evaluated for mineral compositions that show systematic differences between the localities. Grains of native osmium show increases in iridium towards the rim, and nuggets consisting of aggregates define trends of preferential substitution of osmium by iridium. A statistically reliable difference in Os/Ir ratios between the two studied placers can be demonstrated. Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…One was collected from Quaternary sediments in an area of the Ingaringa River (prospecting line L-365, Fig. 2 in Merkle et al, 2012) associated with the Guli clinopyroxene-dunite massif of the Maimecha-Kotui Province in Polar Siberia, Russia (Malitch and Lopatin, 1997). Osmium-iridium-ruthenium alloys from this region typically have 187 Os-isotopic model ages ranging from 545 to 615 Ma and between 65-98 wt.% Os, 1-39 wt.% Ir, and 1-4 wt.% Ru, and may represent a rare example of continental lithospheric mantle material (Table 1; Malitch et al, 2002).…”
Section: Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…One was collected from Quaternary sediments in an area of the Ingaringa River (prospecting line L-365, Fig. 2 in Merkle et al, 2012) associated with the Guli clinopyroxene-dunite massif of the Maimecha-Kotui Province in Polar Siberia, Russia (Malitch and Lopatin, 1997). Osmium-iridium-ruthenium alloys from this region typically have 187 Os-isotopic model ages ranging from 545 to 615 Ma and between 65-98 wt.% Os, 1-39 wt.% Ir, and 1-4 wt.% Ru, and may represent a rare example of continental lithospheric mantle material (Table 1; Malitch et al, 2002).…”
Section: Samplesmentioning
confidence: 99%
“…To more fully investigate the Ru isotopic composition of the oceanic mantle, we report isotopic data for Archean and Phanerozoic materials which were collected from eight oceanic mantle reservoirs. One sample, which likely samples the continental lithospheric mantle (Guli; Malitch and Lopatin, 1997;Merkle et al, 2012), is also included. The Ru isotopic compositions of the IAB iron meteorite complex have previously been reported to match that of the BSE (e.g., Chen et al, 2010;Fischer-Gödde et al, 2015), however, it was subsequently suggested that some IAB iron meteorites had a distinct Ru isotopic composition from the BSE (Fischer-Gödde and Kleine, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Native osmium has also been described in the Guli ultramafic massif in northern Siberia (Malich and Lopatin, 1997;Malitch et al, 2002;Merkle et al, 2012), in ophiolites and Uralian-Alaskan-type complexes (Garuti et al, 1999;González-Jiménez et al, 2009;Melcher et al, 1997;Zaccarini et al, 2005Zaccarini et al, , 2018. Native osmium also been described from placer deposits such as the Witwatersrand in South Africa (Cousins, 1973;Feather, 1976;Malitch and Merkle, 2004;Merkle and Franklyn, 1999) and from various other placers worldwide (Barkov et al, 2018Cabri et al, 1996;Stepanov et al, 2019;Weiser, 2002;Weiser and Bachmann, 1999).…”
Section: Mineral Compositions Of Os-ir-ru Alloysmentioning
confidence: 99%
“…Ablation was carried out with a frequency of 4 Hz, energies of 1-2 mJ/pulse, and a spot size of 15 µm. A standard NiS bead (PGE-A) with 199 ppm Os [68] and 187 Os/ 188 Os = 0.1064 [67], along with a natural Os alloy (i.e., Os 1.0 ) from the Guli massif [69,70], were analyzed between PGM samples to monitor any drift in the Faraday cups. The overlap of 187 Re on 187 Os was corrected by measuring the 185 Re peak and using 187 Re/ 185 Re = 1.6742.…”
Section: Analytical Techniquesmentioning
confidence: 99%